Hip Resurfacing Compared with 28-mm Metal-on-Metal Total Hip Replacement: A Randomized Study with 15 Years of Follow-up*. (4th November 2020) - Vendittoli, Pascal-André; Shahin, Maged; Rivière, Charles; Roy, Alain Guy; Barry, Janie; Lavigne, Martin
Abstract : Background: Bone stock conservation, hip anatomy preservation, and greater stability are among the promoted advantages of hip resurfacing (HR). However, the disappointing failure of some implants nearly led to its abandonment. The aim of this study was to compare clinical scores and revision and complication rates after HR with those after total hip arthroplasty (THA). Methods: Two hundred and three hips were randomized to 28-mm metal-on-metal (MoM) THA (99 hips) or to HR (104 hips). Main outcome measures compared between groups were the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score, the revision rate, and the complication rates. The radiographic findings were also assessed. Results: After a mean follow-up of 15 years (range, 14 to 16 years), 9 (4.4%) of the 203 patients were lost to follow-up and 15 (7.4%) had died. The Kaplan-Meier survivorship, with revision for any reason as the end point, was 89.2% (95% confidence interval [CI], 82.3% to 96.1%) for HR and 94.2% (95% CI, 89.3% to 99.1%) for THA (p = 0.292). The reasons for revision included infection (3 patients), recurrent dislocation (1 patient), and adverse reaction to metal debris (ARMD) (1 patient) in the THA group and ARMD (2 patients) and femoral head loosening (7 patients) in the HR group. With aseptic revision as the end point, the Kaplan-Meier survivorship was significantly higher in the THA group (97.4% versus 89.2%; p = 0.033). No dislocation occurred in the HR group compared with 4 in the THA group (p = 0.058). Both groups achieved a similar mean WOMAC score (10.7 in the HR group and 8.8 in the THA group; p = 0.749), Forgotten Joint Score (87.1 and 85.3, respectively; p = 0.410), University of California Los Angeles (UCLA) activity score (6.3 and 6.4, respectively; p = 0.189), and overall joint perception (p = 0.251). Conclusions: The specific HR and MoM 28-mm THA implants used in this study showed good long-term survival and function. The overall rates of complications and revisions were similar in both groups but were of different types. As it provides better femoral bone preservation and biomechanical reconstruction, HR may continue to have a role in selected patients when performed by experienced surgeons and using validated implants. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.